Application of Security System Legal Documents Reviewer Letters Using Blockchain Technology - Amelia, Sindy; Widya Ningrum, Oktaviana (Blockchain Frontier Technology, 2022)
the popularity of blockchain technology has been widely used in aspects of life in various fields and industries. Because previously blockchain technology was used as crypto or known as digital currency which has developed towards technology and digital is growing rapidly. Where the use of blockchain technology is a new innovation that is increasingly developing in data security systems to suit the times and become one of the modern technologies in the world of education. However, nowadays there are often crimes in the illegal falsification of reviewer letters that can be carried out by irresponsible people for personal interests and can harm the parties concerned. For that we need a data security technology without the need for a third party called blockchain that can maintain the authenticity of the reviewer's letter from the criminal actions of irresponsible parties in forging intentionally or unintentionally. Raharja College has applied blockchain technology to a tool called ABC (data security) and has been implemented on the adimas website which has been going on for two years. Blockchain technology has an encryption hash code or a unique code that is a sign that a letter that has been verified with the blockchain can be seen as different from the original or fake. Because blockchain technology has a level of data security with a block system that is interconnected and has an encryption hash code. This paper uses the literature study method by looking at previous papers with the same theme. This research has the aim that future researchers can produce new innovations in improving data security and improving the quality of technology that can produce new findings in more modern data security systems.